Sosialisasi Pendidikan Karakter Nasionalis di Era Revolusi 4.0 di SMA Negeri 3 Gorontalo - Al Hamid, Saleh; Ngiu, Zulaecha; Sariamas, Ferdiansyah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Globalization and the Fourth Industrial Revolution have transformed the structure of society, including the field of education, where learning activities are increasingly dependent on digital technology. However, this development not only brings convenience but also poses challenges in the form of character degradation among students due to the imbalance between technological proficiency and the cultivation of moral values. This study aims to address that issue by focusing on strengthening nationalist character among students at SMA Negeri 3 Gorontalo through a collaborative approach involving lecturers, university students, and the school itself. The methods employed include reflective educational socialization, character-based digital literacy training, and intensive mentoring to instill national values.The results reveal a remarkable improvement in students’ understanding and awareness of the importance of nationalist character, accompanied by behavioral changes that increasingly reflect national values. Furthermore, the activity fosters synergy between schools and universities in developing adaptive character education in the digital era. The conclusion of this study affirms that the integration of technology with nationalist character education is a strategic solution to shaping a young generation that is not only technologically proficient but also possesses strong character and a solid sense of national identity.ABSTRAKGlobalisasi dan revolusi industri 4.0 telah mengubah tatanan kehidupan masyarakat, termasuk dunia pendidikan, di mana aktivitas pembelajaran semakin bergantung pada teknologi digital. Namun, perkembangan ini tidak hanya membawa kemudahan, tetapi juga tantangan berupa degradasi karakter peserta didik akibat ketidakseimbangan antara penguasaan teknologi dan penanaman nilai-nilai moral. Pengabdian ini bertujuan untuk mengatasi masalah tersebut dengan fokus pada penguatan karakter nasionalis di kalangan siswa SMA Negeri 3 Gorontalo melalui pendekatan kolaboratif antara dosen, mahasiswa, dan sekolah. Metode yang digunakan meliputi sosialisasi edukasi reflektif, pelatihan literasi digital berbasis karakter, serta pendampingan intensif untuk menanamkan nilai-nilai kebangsaan. Hasilnya menunjukkan peningkatan yang luar biasa dalam pemahaman dan kesadaran siswa mengenai pentingnya karakter nasionalis, serta perubahan perilaku yang lebih mencerminkan nilai-nilai kebangsaan. Kegiatan ini juga membangun sinergi antara sekolah dan perguruan tinggi dalam mengembangkan pendidikan karakter yang adaptif di era digital. kesimpulan dari pengabdian ini menegaskan bahwa integrasi teknologi dengan pendidikan karakter nasionalis merupakan solusi strategis untuk membentuk generasi muda yang tidak hanya cakap secara teknologi, tetapi juga berkarakter kuat dan beridentitas kebangsaan yang kokoh.